Władze bezpieczeństwa wobec działalności metropolity Dionizego w latach 1945-1960 = The security authorities towards the activities of metropolitan bishop Dionizy (Dionitius) in the years 1945-1960 - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
After returning to the country in 1945, the metropolitan bishop Dionizy started undertaking actions aiming for the stabilization and creation of normal conditions for the activities of the Orthodox Church. At the same time he emphasized his loyalty towards the Polish nation and country. Despite being involved in Church activities, the authorities strived for removing him from managing the Church.
Keywords: prawosławie - historia - Polska; Dionizy (Waledyński, Konstanty Nikołajewicz; biskup kościoła prawosławnego; 1876-1960); Służba Bezpieczeństwa; Polska - historia; po 1944 r.